The Moderating Effect of Gender and School Type on the Nexus between Soft Skills and TVET Graduates’ Employability - Awodiji, Omotayo Adewale (Journal of Technical Education and Training, 2024)
As the global economy evolves, the need for highly skilled workers becomes increasingly vital. In response to widespread unemployment throughout Africa, TVET programs offer opportunities for citizens to receive professional training. For potential employees, self-perception plays a critical role in their employability. Thus, this study examined the moderating roles of gender and school type in the relationship between soft skills and employability for TVET graduates. Using a survey research design, 327 respondents were systematically sampled and surveyed. The instrument’s reliability was assessed with ordinal alpha coefficients of 0.89 and 0.77. The inferential analysis, specifically -the regression statistic, was used to evaluate the hypotheses at a significance level of 0.05. Hayes model 2 was also used to determine the moderation effects. Results revealed that gender does not moderate the relationship between soft skills and employability, but school type significantly moderated the relationship between soft skills and employability, with graduates from technical colleges having a stronger and more positive relationship between soft skills and employability than those from Brigade schools. To enhance employability, governments, professional institutions, and TVET program administrators should provide development programs on soft skills for educators, regardless of school type, to transfer relevant skills to their learners.